A novel cognitive cueing approach to gait retraining in Parkinson's disease: A pilot study - Stephanie Morrison; Sandi Spaulding; Jeff Holmes; Mary Jenkins (Scholarworks @ WMU, 2015)
Background: Parkinson's disease (PD) impairs gait performance, which can lead to falls and decreased quality of life. This study examined the feasibility of implementing a novel home-based intervention designed to elicit gait improvement in individuals with PD. Methods: Five participants with PD completed a two-week home-based gait retraining intervention designed around guided video feedback. Semi-structured interviews were conducted postintervention and two months postintervention to acquire feedback from the participants about their experience with the intervention. Spatiotemporal parameters of gait and functional mobility were assessed pre and postintervention and at two months postintervention. Results: Participants reported high levels of usability and expressed they believed that the intervention improved their gait and led to a fortified sense of ability and revived sense of empowerment. Comparisons of spatiotemporal and mobility parameters of gait identified that improvements occurred between preintervention and postintervention-step length (x̄ = 10.7%), gait velocity (x̄ = 15.1%), and TUG scores (x̄ = 9.8%)-and between preintervention and two months postintervention-step length (x̄ = 3.9%), gait velocity (x̄ = 9.9%), and TUG scores (x̄ = 4.2%). Conclusions: Guided home-based video training has potential to be an effective treatment strategy for improving gait impairment among individuals with PD.